Kekerasan Aparat terhadap Mahasiswa dalam Perspektif Pelanggaran HAM dan Kegagalan Pedagogis Kritis di Indonesia - Izzatul Afifah; Eko Handoyo (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Violence against student demonstrations in Indonesia continues to become a serious issue in the development of democracy and human rights protection. This study aims to analyze forms of state violence against students from the perspective of human rights violations and critical pedagogy failure. The study uses a qualitative-descriptive approach through literature review methods by examining legal documents, human rights reports, journal articles, and contemporary cases related to student demonstrations in Indonesia. The findings indicate that excessive use of force by security forces, arbitrary arrests, intimidation, and restrictions on freedom of expression reflect systemic violations of civil rights guaranteed by national and international law. Cases during the #ReformasiDikorupsi movement, the rejection of the Criminal Code Bill, and demonstrations against the revision of the TNI Law show the persistence of repressive state practices toward student movements. In the perspective of Paulo Freire’s critical pedagogy, violence against students demonstrates the failure of democratic education because students are treated as objects of control rather than critical subjects in public discourse. This condition weakens academic freedom, narrows democratic spaces, and creates fear within academic environments. The study concludes that violence against student movements is not merely a legal issue but also a structural crisis in democratic education and human rights protection in Indonesia.